1986
DOI: 10.1177/004051758605600901
|View full text |Cite
|
Sign up to set email alerts
|

Never Dried Cotton Fibers Have a Circular Cross Section

Abstract: The shape of the fiber in the cotton boll just before natural dehydration was studied by different preparation techniques. The results all pointed to the fact that never dried fibers have a circular cross section. Therefore, a simple observation of never dried fibers on equatorial optical plane provides a correct evaluation of basic dimensional parameters such as section diameter and wall thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…' For never dried fibm W = P/1f [10]. &dquo;For soda swollen 6bers on equatorial section P = P' (see text).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…' For never dried fibm W = P/1f [10]. &dquo;For soda swollen 6bers on equatorial section P = P' (see text).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the collapsed fibers probably turned over, so that we observed the widest ribbon width. Since the never dried fibers have a circular cross section [10] and since the technique for observing fibers in the equatorial optical plane prevented any squeezing of the fibers, this gentle pressure had no influence on the ribbon width of never dried fibers observed in equatorial optical section. The most striking fact is that the 2E of soda swollen fibers in the equatorial optical plane was almost twice the 2E observed in cross sections of the same fibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase lasts for 50 d after the beginning of fiber initiation until the boll opens or until environmental factors stop the physiological advancement of the boll (Abidi et al., 2008). Soon after the boll opens, the cotton fibers dry and collapse, forming kidney bean–shaped cross‐sections (Peeters, Wijsmans, De Langhe, De Langhe, & Waterkeyn, 1986).…”
Section: Relationship Of Boll Distribution and Fiber Qualitymentioning
confidence: 99%
“…In general, the width of the ribbon shall be as wide as the diameter if the object has a cylindrical tube structure. Previous studies revealed that cotton bers develop as cylindrical tubes and have a circular cross-section in the boll just before they lose their moisture (27). However, when cotton is dried naturally, the tube structure collapses and forms a at ribbon-like structure of uneven diameter or irregular crosssections with recurring convolutions or twists along the length of the ber (5,(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%